KNOWLEDGE SHARING AS AN INNOVATIVE LEARNING METHOD IN IMPLEMENTATION OF “MERDEKA BELAJAR-KAMPUS MERDEKA” - Pradewi, Gunarti Ika; Chailani, Muchammad Iqbal (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Merdeka belajar-kampus merdeka (MBKM) is a policy that is implemented in universities. This policy gives the students flexibility to add competencies that are useful for their lives. The existence of this flexibility is also inseparable from the challenges faced. One of the challenges faced is the challenge in the field of student literacy skills. In this study, researchers looked at the effectiveness of the knowledge sharing method to improve student literacy and support the implementation of “Merdeka Belajar”. This research was conducted at a university in Temanggung. This study used a classroom action research method with a spiral model from Kemmis and Taggart. The results show that the success of knowledge sharing in the context of “merdeka belajar” is influenced by: the ability to read and understand a text, the ability to express opinions and explain, the ability to self-directed learning, and the ability to understand sharing from friends.